The inadequacy of the ρ-T curve for phase transitions in the presence of magnetic fields - Shengnan Zhang; Zhong Fang; Hongming Weng; Quansheng Wu (The Innovation)
The resistivity-temperature (ρ(T)) curve is traditionally employed to distinguish metallic, semiconducting, and insulating behaviors in materials, with deviations often interpreted as evidence of phase transitions. However, such interpretations are valid only under specific conditions, including the presence of a magnetic field. This study critically reexamines the ρ(T) curve in magnetic environments. Our findings reveal that shifts between metallic and insulating states, as well as reentrant metallic behavior, may not necessarily indicate genuine phase transitions. Instead, these phenomena can be attributed to the scaling behavior of magnetoresistance, governed by a power law dependence on both the magnetic field and temperature. Employing first-principles calculations and the Boltzmann transport method, we analyzed the magnetoresistance of SiP2 and NbP across varying conditions. This approach not only explains the reentrant behavior observed experimentally but also reconciles discrepancies in magnetoresistance findings reported by different research groups. These findings challenge the conventional reliance on the ρ(T) curve as a straightforward indicator of phase transitions in magnetic fields. We underscore the importance of accounting for standard magnetoresistance effects caused by the Lorentz force before confirming the existence of such transitions. This novel perspective advances our understanding of material properties in magnetic fields and establishes a new framework for interpreting transport phenomena in condensed matter physics.